The effect of bronchial thermoplasty on airway volume measured 12 months post-procedure - Langton, David (ERJ Open Res, 2020)
Bronchial thermoplasty induces atrophy of the airway smooth muscle layer, but the mechanism whereby this improves patient health is unclear. In this study, we use computed tomography (CT) to evaluate the effects of bronchial thermoplasty on airway volume 12 months post-procedure. 10 consecutive patients with severe asthma were evaluated at baseline by the Asthma Control Questionnaire (ACQ), and high-resolution CT at total lung capacity (TLC) and functional residual capacity (FRC). The CT protocol was repeated 4 weeks after the left lung had been treated by bronchial thermoplasty, but prior to right lung treatment, and then again 12 months after both lungs were treated. The CT data were also used to model the implications of including the right middle lobe (RML) in the treatment field. The mean patient age was 62.7±7.7 years and forced expiratory volume in 1 s (FEV(1)) 42.9±11.5% predicted. 12 months post-bronchial-thermoplasty, the ACQ improved, from 3.4±1.0 to 1.5±0.9 (p=0.001), as did the frequency of oral steroid-requiring exacerbations (p=0.008). The total airway volume increased 12 months after bronchial thermoplasty in both the TLC (p=0.03) and the FRC scans (p=0.02). No change in airway volume was observed in the untreated central airways. In the bronchial thermoplasty-treated distal airways, increases in airway volume of 38.4±31.8% at TLC (p=0.03) and 30.0±24.8% at FRC (p=0.01) were observed. The change in distal airway volume was correlated with the improvement in ACQ (r=−0.71, p=0.02). Modelling outputs demonstrated that treating the RML conferred no additional benefit. Bronchial thermoplasty induces long-term increases in airway volume, which correlate with symptomatic improvement.